The rising star of 2D black phosphorus beyond graphene: synthesis, properties and electronic applications. (6th October 2017) - Chen, Pengfei; Li, Neng; Chen, Xingzhu; Ong, Wee-Jun; Zhao, Xiujian
Abstract: Black phosphorus, which is a relatively rare allotrope of phosphorus, was first discovered by Bridgman in 1914. Since the advent of two-dimensional (2D) black phosphorus (which is known as phosphorene due to its resembling graphene sheets) in early 2014, research interest in the arena of black phosphorus was reignited in the scientific and technological communities. Henceforth, a myriad of research studies on this new member of the 2D world have been extensively emerged. Fascinatingly, 2D black phosphorus exhibits a distinctive wrinkled structure with the high hole mobility up to 1000 cm 2 V −1 s −1, excellent mechanical properties, tunable band structures, anisotropic thermal, electrical and optical properties, thus leading to its marvelous prospects in device applications. This review firstly introduces the state-of-the-art development, structural properties and preparation routes of black phosphorus. In particular, anisotropy involved in mechanical properties, thermal conductivity, carrier transport as well as optical properties is comprehensively discussed. Apart from discussing the recent progress in black phosphorus which is applied to devices (i.e. field effect transistors and optoelectronic), the review also highlights the bottlenecks encountered by the society and finally casts an invigorating perspective and insightful outlook on the future direction of the next-generation 2D black phosphorus by harnessing its remarkable characteristics for energy production.